Status and prospects of Nasidman Island marine protected area Ajuy, Iloilo - Cuesta, Efren G. (University of the Philippines in the Visayas, 2004)
The present status and prospects of Nasidman Island MPA was examined in this study within the three-month period (Nov 2002-Feb 2003) through the conduct of interview using survey questionnaire and actual fish catch monitoring on daily basis. A total of fifteen (15) fishermen comprised the correspondents of this study for the actual monitoring of fish catch and sixty-one (61) fishing families comprising 25% of the total fishing families from the three barangays were also interviewed using the questionnaire. A total of 93 days has been spent in monitoring fish catch data from the three (3) sampling sites (barangays). Brgy. Malayu-an has the highest Average CPUE(kg/day) of 3.35; and 2.74 and 1.47 for Brgys. Nasidman and Barrido, respectively. Brgy Nasidman has the highest average CPUE (kg/hr) of 0.61; and 0.50 and 0.21 for Brgys. Malayu-an and Barrido, respectively. On the average, Brgy Nassidman has the lowest number of hours spent in fishing per day (4.36), followed by Brgys. Malayu-an (6.80) and Barrido (6.93). There exist a consistency in findings between the structured interview conducted and the actual fish catch monitoring system employed in this study. As observed,the type of fishing gear used, number of hours spent in fishing, accessibility to fishing ground, weather condition and status of the fishing ground were the factors that affect the fishing effort. Likewise, factors that affect the present condition of the MPA in Nasidman Island were identified as follows: (a) zoning schemes was not considered before establishing the MPA project, and (b) regulations related to resource-use within the area were not properlyformulated in as much as to avoid overfishing and biodiversity depletion. One outstanding recommendation for this study is to encourage the municipality to legitimize the MPA in Nasidman Island through a Municipal Ordinance and devise a zoning scheme of which. The 40 hectares existing MPA must be made as a core zone for preservation and protection. Nofishing and other forms of extractive and exploitative activities within the core zone shall be permitted. A 500 meters buffer zone must be established and the area outside of which shall serve as a source of sustainable fishing ground for hook and line fishing. Establishment and deployment of artificial reefs in the core and buffer zone is also recommended in order to promote and enhance regeneration of degraded habitats and revive its biodiversity.